Transparent analysis of compression damage propagation of freeze-thaw rock based on CT-DVC - Liu, Hui; Liu, Mengjie; Yang, Gengshe; Shen, Yanjun; Liang, Bo; Ding, Xiao; Dai, Xinyue; Zhu, Minkai; Wang, Runqi (Cold regions science and technology, 2025)
Observing and quantifying the discontinuous structural evolution of rocks under thermo-mechanical loading remains a key challenge in cold region rock mechanics. CT real-time scanning of freeze-thaw sandstone under coupled loading captured 3D digital images of damage structures during uniaxial compression. A local 3D digital volume correlation (DVC) method with the Inverse Compositional Gauss-Newton (IC-GN) algorithm enabled non-contact measurement of internal deformations during compression failure. Full-field 3D strain distributions and damage characteristics were quantified under thermo-mechanical conditions. The method quantitatively visualized internal damage deformation, showing that the sandstone's meso-structure provides an effective DVC carrier. IC-GN-based analysis revealed that macro-damage propagates along pre-existing meso-damage paths under compressive loading, with initial damage structures dictating crack propagation directions and spatial distribution patterns at failure. As loading intensifies, localized deformation zones progressively coalesced with failure regions, while strain field distribution correlates consistently with crack morphology during sandstones rupture. The peak porosity of rock specimens at failure progressively rises under repeated freeze-thaw cycles. This research advances transparent analysis of discontinuous structures and multi-physical field effects, offering insights for frost damage mitigation in cold region engineering. •In-situ CT real-time scanning reveals sandstone damage under coupled freeze-thaw and loading.•Novel 3D deformation analysis integrates DVC with CT-based structural identification.•Non-contact 3D damage mapping in freeze-thaw rock during compressive failure.•Local 3D digital volume correlation via IC-GN registration algorithm.•Quantitative 3D visualization of meso-damage evolution in freeze-thaw rock.